Determination of Polyphenols in Ilex kudingcha and Insect Tea (Leaves Altered by Animals) by Ultra-high-performance Liquid Chromatography-Triple Quadrupole Mass Spectrometry (UHPLC-QqQ-MS) and Comparison of Their Anti-Aging Effects - Mu, Jianfei; Yang, Fuping; Tan, Fang; Zhou, Xianrong; Pan, Yanni; Long, Xingyao; Zhao, Xin (Frontiers in Pharmacology, 2021)
Ilex kudingcha C.J. Tseng tea and insect tea, as traditional Chinese teas, are favored for their original craftsmanship, unique flavor, and biological functionality. In this study, ultra high-performance liquid chromatography-triple quadrupole mass spectrometry (UHPLC-QqQ-MS) was used to analyze the bioactive components of the extracts of Ilex kudingcha and insect tea, and D-galactose-induced aging mice were used to compare the in vivo anti-aging effects of Ilex kudingcha and insect tea extracts. The results were remarkable, UHPLC-QqQ-MS analysis showed that ITP contains kaempferol, narirutin, protocatechuic acid, caffeic acid, phloretin, taxifolin, isochlorogenic acid A, isochlorogenic acid B, isochlorogenic acid C, and phloridzin. Chlorogenic acid, cryptochlorogenic acid, p-coumaric acid, isoquercitrin, and hesperidin accounted for 65% of the total content in IKDCP. However, due to the large differences in the content of the main chemical components in IKDCP and ITP, the effects are also different. At the same time, suggesting that the anti-aging effects of IKDCP and ITP (500 mg/kg) include the regulation of viscera indices of major organs; improvement in liver, skin, and spleen tissue morphology; decreased production of inflammatory cytokines; up regulation of SOD, CAT, GSH, GSH-PX, and T-AOC and down regulation of NO and MDA levels in serum and liver tissue; reductions in the concentration of pro-inflammatory factors (IL-6, TNF-α, and IL-1β), and increases in the concentration of anti-inflammatory factor IL-10. RT-qPCR and western blot assay also showed that IKDCP and ITP affect anti-aging by regulating the gene and protein expression of GSH-PX, GSH1, SOD1, SOD2, and CAT. The overall results indicate that ITP is more effective in treating oxidative damage in aging mice induced by D-galactose. Thus, ITP appears to be an effective functional drink due to its rich nutritional components and anti-aging activities.